Mediators in the Association Between Affective Temperaments and Suicide Risk Among Psychiatric Inpatients. Issue 3 (3rd July 2018) - Erbuto, Denise; Innamorati, Marco; Lamis, Dorian A.; Berardelli, Isabella; Forte, Alberto; De Pisa, Eleonora; Migliorati, Monica; Serafini, Gianluca; Gonda, Xenia; Rihmer, Zoltan; Fiorillo, Andrea; Amore, Mario; et al.
Abstract : Background : Affective temperaments have been shown to be related to psychiatric disorders and suicidal behaviors. Less is known about the potential contributory role of affective temperaments on suicide risk factors. In the present study, we investigated whether the effect of affective temperaments on suicide risk was mediated by other variables, such as hopelessness, mentalization deficits, dissociation, psychological pain, and depressive symptoms. Methods : Several assessment instruments, including the Mini International Neuropsychiatric Interview (MINI); the Temperament Evaluation of Memphis, Pisa, and San Diego Autoquestionnaire (TEMPS-A); the Beck Hopelessness Scale (BHS); the Gotland Male Depression Scale (GMDS); the Dissociative Experiences Scale (DES); the Psychological Pain Assessment Scale (PPAS); and the Mentalization Questionnaire (MZQ), were administered to 189 psychiatrically hospitalized patients (103 women, 86 men) in Rome, Italy. Results : In single-mediator models, hopelessness, depressive symptoms, and mentalization, but not psychological pain or dissociation, were significant mediators in the association between prevalent temperament and suicide risk. In a multiple-mediator model, a significant indirect effect was found only for depression. Results demonstrated that patients with negative temperaments reported higher suicide risk, psychological pain, hopelessness, and depression, and less mentalization than patients with no prevalent temperament or hyperthymic temperaments. Conclusions : Hopelessness, depression, and mentalization are all factors that mediate the relation between affective temperaments and suicide risk. Identifying factors that mediate the effects of affective temperamental makeup on suicide risk should enhance screening and intervention efforts.